Positive because it is above zero meaning more. if it has more than it could not be a negative because negatives are numbers to the left on a number line meaning less than zero.
Answer:
![\sf \dfrac{1}{10}](https://tex.z-dn.net/?f=%5Csf%20%5Cdfrac%7B1%7D%7B10%7D)
Step-by-step explanation:
From the table:
- Total number of Sophomores = 10
- Total number of students = 37
- Total number of Boys who are Sophomores = 1
![\sf Probability \ of \ an \ event \ occurring = \dfrac{Number \ of \ ways \ it \ can \ occur}{Total \ number \ of \ possible \ outcomes}](https://tex.z-dn.net/?f=%5Csf%20Probability%20%5C%20of%20%5C%20an%20%5C%20event%20%5C%20occurring%20%3D%20%5Cdfrac%7BNumber%20%5C%20of%20%5C%20ways%20%5C%20it%20%5C%20can%20%5C%20occur%7D%7BTotal%20%5C%20number%20%5C%20of%20%5C%20possible%20%5C%20outcomes%7D)
![\sf \implies P(Sophomore)=\dfrac{10}{37}](https://tex.z-dn.net/?f=%5Csf%20%5Cimplies%20P%28Sophomore%29%3D%5Cdfrac%7B10%7D%7B37%7D)
![\sf \implies P(Boy \cap Sophomore)=\dfrac{1}{37}](https://tex.z-dn.net/?f=%5Csf%20%5Cimplies%20P%28Boy%20%5Ccap%20Sophomore%29%3D%5Cdfrac%7B1%7D%7B37%7D)
![\begin{aligned}\sf P(Boy | Sophomore) & = \sf\dfrac{P(Boy \cap Sophomore)}{P(Sophomore)}\\\\ & = \sf \dfrac{1}{37} \div \dfrac{10}{37}\\\\ & = \sf\dfrac{1}{37} \times\dfrac{37}{10}\\\\ & = \sf\dfrac{1}{10}\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%5Csf%20P%28Boy%20%7C%20Sophomore%29%20%26%20%3D%20%5Csf%5Cdfrac%7BP%28Boy%20%5Ccap%20Sophomore%29%7D%7BP%28Sophomore%29%7D%5C%5C%5C%5C%20%26%20%3D%20%5Csf%20%5Cdfrac%7B1%7D%7B37%7D%20%5Cdiv%20%5Cdfrac%7B10%7D%7B37%7D%5C%5C%5C%5C%20%26%20%3D%20%5Csf%5Cdfrac%7B1%7D%7B37%7D%20%5Ctimes%5Cdfrac%7B37%7D%7B10%7D%5C%5C%5C%5C%20%26%20%3D%20%5Csf%5Cdfrac%7B1%7D%7B10%7D%5Cend%7Baligned%7D)
Answer:
Step-by-step explanation:
Let and be independent random variables representing the lifetime (in 100 hours) of Type A and Type B light bulbs, respectively. Both variables have exponential distributions, and the mean of X is 2 and the mean of Y is 3.
Answer:
8
Step-by-step explanation:
Given algebraic expression:
5(x - 1) - 2
To:
Evaluate this expression using x = 3
Solution:
Evaluate by plugging x = 3 to this expression:
Simplify using PEMDAS.
<u>We can conclude:</u>
By evaluating x = 3 to the given expression,the answer will be 8.
7 1/2 = 15/2
Multiply 7 and 2, then add 1 = 15
Keep the denominator
3 2/3 = 11/3
Multiply 3 and 3, then add 2 = 11
Keep the denominator